Cartographies of the tactic: : Everyday resistance and spatial insurgency in Divakaruni’s Oleander girl - Pourya Asl, Moussa (International Journal of English Studies, 2026)
This article explores the politics of quotidian resistance in Chitra Banerjee Divakaruni’s Oleander girl (2013) using Michel de Certeau’s theorization of tactics and strategies. It conceptualizes space and time as active, contested terrains where subaltern agency is enacted through subtle, embodied, and affective practices. The protagonist, Korobi Roy, resists patriarchal, caste-bound, and diasporic-nationalist constraints not via overt confrontation, but through micro-gestures –secret readings, sartorial transgressions, strategic silences, spatial reappropriations– that tactically infiltrate and refunction the architectures of control. These acts, often dismissed as inconsequential, cumulatively inscribe an alternative cartography of belonging, one that refuses full legibility within dominant frameworks. By analyzing Korobi’s navigations across Kolkata’s domestic interiors and post-9/11 New York’s securitized streets, the study shows diasporic female subjectivity can be constituted in –and through– interstices of hegemonic systems. In doing so, it reframes agency as immanent to constraint, privileging opacity, improvisation, and affective insurgency over visibility or strategic sovereignty.